The probiotic Companilactobacillus crustorum MN047 alleviates colitis-associated tumorigenesis via modulating the intestinal microenvironment. Issue 22 (20th October 2021) - Wang, Tao; Wang, Panpan; Ge, Wupeng; Shi, Chao; Xiao, Gongnian; Wang, Xin; Lü, Xin
Abstract : This study investigated the protective effect of C. crustorum MN047 on the AOM/DSS-induced CA-CRC mice, as demonstrated by the amelioration of gut barrier damage, inflammation and regulation of gut microbiota. Abstract : Supplementation of probiotics is a promising method to alleviate colorectal cancer (CRC) via modulating the intestinal microenvironment. This study aimed to assess the potential anti-CRC effect of Companilactobacillus crustorum MN047 on an azoxymethane and dextran sulfate sodium-induced colitis-associated (CA)-CRC mouse model. Mice were gavaged with C. crustorum MN047 once daily (∼1 × 10 9 CFU per mouse). The CA-CRC ameliorating effect of this strain was investigated based on the gut microbiota, inflammation and intestinal barrier integrity. Results showed that C. crustorum MN047 could significantly attenuate tumorigenesis and inflammation via suppressing the TLR4/NF-κB pathway. Moreover, this probiotic could improve the intestinal barrier integrity by increasing the mRNA level of some tight junction-related proteins and reducing goblet cell loss. In addition, C. crustorum MN047 administration led to an increase in beneficial bacteria and a decrease in harmful bacteria, thereby increasing SCFAs and reducing LPS levels. These results suggested that C. crustorum MN047 could partially ameliorate the formation of CA-CRC by modulating the gut microbiota, attenuating inflammation and enhancing the intestinal barrier integrity. Therefore, C. crustorum MN047 was a promising probiotic supplement for attenuating CA-CRC.